Is The Investment Account The Blue Ocean of Islamic Banking? - Syafril, Syafwendi (International Journal of Islamic Finance, 2023)
Background: Profit-Loss Sharing (PLS) and prohibition of interest are fundamental principles of Islamic banking. However, Islamic banking practice today seems move away from the ideal concept which is promoting PLS. Most of Islamic bank engage with less risky product and heavily relies on debt-based financing such as Murabaha. Objectives: This study aims to discuss the opportunity and challenge in offering PLS instrument to financial customer as blue ocean strategy of Islamic bank. Novelty: Islamic bank is expected to increase the portion of PLS instrument by offering investment account to support real sector growth. Additionally, this study provides economic rationale behind PLS instrument that Islamic banking may take into account. Research Methodology / Design: a qualitative approached is employed to identify the challenge and opportunity of using PLS in investment account. Data is collected from journal articles, book, and other documented sources. The content analysis is performed to investigate economic rationale behind investment account product and factors that make the instrument less popular among Islamic banking institution Findings: Profit and sharing investment account (PSIA) helps to overall employment creation by investing in real economic sector developments. Additionally, PSIA creates potential for equitable income distribution through wise capital allocation, by channeling capital units to micro, small, and medium-sized firms. Implication: The study can enrich Islamic finance literature in area of Islamic banking with regard to utilization of profit and sharing instrument for supporting real economic sector.